Exploration of numeracy in digital cultural content - Ni Luh Sakinah Nuraini; Puri Selfi Cholifah; Santy Dinar Permata; Davina Aurelia; Silva Nabilla; Cempa Huzaimah (Educational Challenges)
The PISA results of 2022 awarded Indonesian students poor scores in literacy and numeracy. Previous studies have suggested that numeracy skills can be improved by applying game-based learning to ethnomathematics. Therefore, a similar strategy was explored, in the form of digital content based Culturally Responsive Teaching (CRT).